Characteristics of personally important episodic memories, counterfactual thoughts, and future projections across age and culture. Issue 5 (11th May 2020) - Özbek, Müge; Bohn, Annette; Berntsen, Dorthe
Summary: We have limited knowledge as to whether the phenomenological differences between episodic memories, counterfactuals, and future projections show the same pattern across age groups and diverse samples. Here we compared the characteristics of these mental events, reported by younger and older participants in a Turkish (Study 1) and in an American sample (Study 2). In both studies, memories contained more sensory‐perceptual‐spatial details, were easier to bring to mind, and more specific. Future projections were the most positive, whereas counterfactuals were the least emotionally intense. In Study 1, older participants rated the events more positively and experienced them with more perceptual detail, whereas younger participants reported the future to be more voluntarily rehearsed, important, and central. These age differences did not replicate in Study 2. Overall, phenomenological differences between the events are robust and replicate across diverse samples. However, age differences are more sensitive to cultural or individual differences.